Psychological Status of High School Students 1 Year After the COVID-19 Emergency - Zhou, Cong; Li, Rongqin; Yang, Mingchuan; Duan, Shanshan; Yang, Chuanming (Frontiers in Psychiatry, 2021)
Background: With the control of the epidemic, adolescents' mental outlook might have improved. However, little evidence existed with regard to the psychological status of adolescents in post-COVID-19 era. This present study aimed to explore the psychological status of high school students after the epidemic getting eased. Methods: A web-based cross-sectional survey was used to obtain data from three high schools, including the demographic information, the Patient Health Questionnaire-9 (PHQ-9), the Generalized Anxiety Disorder-7 (GAD-7), the Self-Rating Scale of Sleep (SRSS) and self-designed general recent-status questionnaire. Correlation analysis was performed to explore potential associations between the depression symptoms, anxiety symptoms and sleep status. The PHQ-9 and GAD-7 differences between nowadays data and the data enrolled 12 months before were also compared. Result: A total of 1108 qualified questionnaires were obtained. The prevalence of depressive and anxious symptoms was 27.5% and 21.3%, respectively, from mild to severe in all students, while 11.8% of these high students got sleep disturbances. Both the rate and the severity of depression, anxiety and sleep problems of female students were higher than male students. Grade three students surfered higher prevalence and severer mental disturbances than the other two grades. There were significant correlations between the depression symptoms, anxiety symptoms and sleep status. The psychological status has been improved in nowadays high school students compared with the sample enrolled 12 months before. Conclusion: As a supplement to our former study, this present research provided a perspective on the psychological status of high school students one year after the COVID-19 Pandemic being well controlled. We should pay attention to the psychological status of high school students, and should also notice the progresses made by this special group after the epidemic.